THE RELATIONSHIP BETWEEN STUDENTS' CRITICAL THINKING SKILLS ON THE INDICATORS OF INFERRING AND PROVIDING FURTHER EXPLANATION AT JUNIOR HIGH SCHOOL 17 MAKASSAR - Arif, Rifda Nur Hikmahwati; Sofyan, Ryan Rayhana; Arif, Rifda Mardian (JTechLP: Journal of Technology in Language Pedagogy, 2022)
This study aims to determine the relationship between the Critical Thinking Skills of Students on Indicators of Concluding and Providing Further Explanation. The population in this study were all students in grade VIII of SMP SMPN 17 Makassar, totaling 290 students and spread across 10 different classes. This research is a descriptive correlative study with a quantitative approach. Sampling was selected using a purposive sampling technique. The sampling technique in this study was to use a saturated sampling technique so the total sample in this study was 290 students. The data were then processed by descriptive statistical analysis with normality test, significance test, mean, median, mode, standard deviation, and coefficient of determination. This study uses the Pearson correlation technique. The results show that there is a very low correlation between critical thinking skills in giving simple explanations and building basic skills categorized as very low with a value of 0.17.